(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Influence of Vipera lebetina obtusa venom on level of free-radical oxidation of homogenates and lipids, purified from nervous tissue of poikilothermal and homothermal vertebrates was studied using chemiluminescence and spectrophotometric measurement of malonic dialdehide concentration. It was shown that action of toxin leads to inhibition of this process, which probably is accounted for antioxidant mechanism of interaction. Manifestation of this effect is not similar for every of studied organisms. This phenomenon may be related to the degree of saturation in fatty acids of lipids in researched tissue of different vertebrates.